Visualisasi Data Faktor yang Mempengaruhi Customer Churn Menggunakan Tableau - Nurwigian, Hanifatul; Voutama, Apriade (Jurnal Nasional Ilmu Komputer, 2025)
Customer churn is a phenomenon when customers stop using the services of a particular company and switch to services from another company. This phenomenon is very detrimental to the company, especially in terms of finance and reputation. Therefore, the Company needs to deal with this problem by designing an effective strategy. This study aims to create a data visualization in the form of a dashboard using the Tableau tool. In this study, descriptive analysis is used to draw conclusions and design strategies in dealing with customer churn problems. Based on the visualization results, it was found that the customer churn phenomenon tends to occur at the beginning of the subscription period, especially in the first month, and customers who choose the month-to-month contract type tend to experience churn. In addition, the payment method and type of internet service selected by the customer also affect the churn rate.